2018
DOI: 10.1080/09603123.2018.1522423
|View full text |Cite
|
Sign up to set email alerts
|

Presence of carbapenem-resistant bacteria in soils affected by illegal waste dumps

Abstract: The carbapenem-resistant bacteria (CRB) are currently at the top of the WHO priority list of bacteria that pose the greatest threat to human health. Considering that soil is one of the important environments for the emergence of antibiotic-resistant bacteria, we isolated and quantified cultivable CRB in soils across Croatia, including ones affected by illegal dumps. We cultivated CRB at two temperatures, distinguishing between the intrinsically resistant CRB (37°C, mostly Stenotrophomonas spp.) and the ones th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 36 publications
3
21
0
Order By: Relevance
“…In the future, as we expand our studies to additional soil samples and locations, it will be interesting to analyze our samples at both 37°C and 42°C to compare the abundance and diversity of CRB obtained at both temperatures. However, of the 40 CRB isolates identified and characterized in the present study, only 11 of them (from 3 different soil samples) were S. maltophilia (Tables 2 and 3), and we were able to isolate, among other CRB, carbapenem‐resistant (CR) Cupriavidus, and Pseudomonas strains, as reported by Hrenovic et al (2019) at 42°C. These findings suggest that, although S. maltophilia may be an important contributor to the abundance and wide distribution of CRB found in the soils we analyzed, other CRB were also an important factor.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…In the future, as we expand our studies to additional soil samples and locations, it will be interesting to analyze our samples at both 37°C and 42°C to compare the abundance and diversity of CRB obtained at both temperatures. However, of the 40 CRB isolates identified and characterized in the present study, only 11 of them (from 3 different soil samples) were S. maltophilia (Tables 2 and 3), and we were able to isolate, among other CRB, carbapenem‐resistant (CR) Cupriavidus, and Pseudomonas strains, as reported by Hrenovic et al (2019) at 42°C. These findings suggest that, although S. maltophilia may be an important contributor to the abundance and wide distribution of CRB found in the soils we analyzed, other CRB were also an important factor.…”
Section: Discussionsupporting
confidence: 76%
“…Moreover, although different soil locations were tested in both studies, our findings, as well as those from Djenadi et al (2018), suggest that at 37°C, using MacConkey medium instead of CHROMagar might contribute to isolating more diverse CRB, even without using 42°C to suppress the growth of S. maltophilia . Also, CR Pseudomonas were the most abundant (15 out of 40 CRB identified in our study) CRB we found, compared to only one CR Pseudomona s isolate identified by Hrenovic et al (2019) at 42°C. Although further studies analyzing the same soil samples with both growth media and temperatures are necessary, this finding suggests that isolation of CRB at 42°C may not only suppress the growth of S. maltophilia , but also of closely related Pseudomonas .…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations